Branched‐Selective Direct α‐Alkylation of Cyclic Ketones with Simple Alkenes. Issue 13 (21st February 2019) - Xing, Dong; Qi, Xiaotian; Marchant, Daniel; Liu, Peng; Dong, Guangbin
Abstract: Herein, we describe an intermolecular direct branched‐selective α‐alkylation of cyclic ketones with simple alkenes as the alkylation agents. Through an enamine‐transition metal cooperative catalysis mode, the α‐alkylation is realized in an atom‐ and step‐economic manner with excellent branched selectivity for preparing β‐branched ketones. Employment of a pair of bulky Brønsted acid and base as additives is responsible for enhanced efficiency. Promising enantioselectivity (74 % ee ) has been obtained. Experimental and computational mechanistic studies suggest that a pathway through alkene migratory insertion into the Ir−C bond followed by C−H reductive elimination is involved for the high branched selectivity. Abstract : An intermolecular direct branched‐selective α‐alkylation of cyclic ketones has been achieved using simple alkenes as the alkylation agents. 7‐Azaindoline is employed as a bifunctional ligand to facilitate enamine formation and guide subsequent C−H activation with an iridium catalyst. This method offers a straightforward and byproduct‐free means to access ketones with β‐stereocenters.